2016
DOI: 10.1371/journal.pone.0151627
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A and the Prevention of Hypertrophic Scars on the Maxillofacial Area and Neck: A Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundThe purpose of the meta-analysis was to evaluate the efficiency of therapeutic botulinum toxin type A (BTX-A) in the prevention of maxillofacial and neck scars.Methods and FindingsInformation came from the following electronic databases: Medline, PubMed, Cochrane Library, and EMBASE (time was ended by August 31, 2015) to retrieve RCTs evaluating the effect of the BTX-A for hypertrophic scar on the maxillofacial or neck. All languages were included as long as they met the inclusion criteria. Here the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 34 publications
0
24
0
1
Order By: Relevance
“…1,26 A recent meta-analysis demonstrated that botulinum toxin significantly reduced the width of hypertrophic scars, improved their appearance on visual analog scales, and improved overall patient satisfaction. 27 Botulinum toxin does not have an immediate onset of action; however, when used as an adjunct during scar revision, patients should undergo injection 2 weeks prior to surgical revision. 1…”
Section: Botulinum Toxinmentioning
confidence: 99%
“…1,26 A recent meta-analysis demonstrated that botulinum toxin significantly reduced the width of hypertrophic scars, improved their appearance on visual analog scales, and improved overall patient satisfaction. 27 Botulinum toxin does not have an immediate onset of action; however, when used as an adjunct during scar revision, patients should undergo injection 2 weeks prior to surgical revision. 1…”
Section: Botulinum Toxinmentioning
confidence: 99%
“…Moreover, some animal studies demonstrated the usefulness of BTX in scar and keloid reduction [20], [21], [22]. Despite all differences in published studies a recent meta-analysis of randomised controlled trials evaluating BTX effect in the face/neck area has found that patients who received BTX had better outcomes than those who did not receive it [24]. According to this study the scars were significantly narrower ( P = 0.006) and visual analogue scale scores were significantly better, indicating that patients treated with BTX were more satisfied with the results than those who received saline.…”
Section: Resultsmentioning
confidence: 99%
“…22 The analysis found that scars were significantly narrower ( P = 0.006) and visual analog scale (VAS) scores were significantly higher, indicating that patients receiving BoNT-A were more satisfied with the results than those who received saline. However, the number of studies eligible for the analysis was small (9) and only 3 were unbiased in all assessment domains.…”
Section: Aesthetic Developmentsmentioning
confidence: 97%